Enhanced lubricity of CVD diamond films by in-situ synthetization of top-layered graphene sheets. (30th October 2021) - Ji, Zhe; Lin, Qiang; Huang, Zhewei; Chen, Sulin; Gong, Peng; Sun, Zhengzong; Shen, Bin
Abstract: In the present study, we demonstrated a novel process of in-situ fabrication of graphene sheets by adopting the chemical vapor deposition (CVD) method. Fabricating such a layer of vertical graphene sheets (VGs) on the surface of microcrystalline diamond (MCD) films could decrease the stable coefficient of friction (COF) by 20–30%. Besides, such lubricity showed excellent load capacity and durability. With normal loads ranging from 3 N to 9 N (Hertz contact pressure of 2.1–3.1 GPa), the MCD-VGs films exhibited COFs stabilized at 0.105 and wear rates less than 5 × 10 −6  mm 3  N −1  m −1 . Additionally, the produced VGs displayed an excellent service lifetime with 72, 000 sliding cycles. During the friction tests, an equilibrium graphene self-mated contact formed on the sliding interface as graphene fragments adhered onto the counterpart ball and resulted in the reduction of friction and low wear rates. Additionally, the mixtures of Si3 N4 /SiO2 particles and graphene sheets residual within the wear tracks would promote the transformation of the sliding regime to three-body abrasion, beneficial for friction reduction. The findings presented in this study provide a novel and effective approach to enhance the lubricity of any engineering diamond surface. Graphical abstract: Image 1 Highlights: In-situ fabricating vertical graphene sheets (VGs) on the diamond surface. The top-layered VGs reduce the stable COF of MCD films by 20%–30%. The lubricity of the top-layered VGs exhibits excellent load capacity up to 3.1 GPa. The wear rates of VGs-coated MCD film are less than 5 × 10 −6 mm 3 N −1 m −1 .